PELATIHAN PEMBUATAN MEDIA PEMBELAJARAN DORATOON BERMUATAN KEARIFAN LOKAL BAGI GURU SEKOLAH DASAR KECAMATAN PAMIJAHAN KABUPATEN BOGOR - Lestari, Hana; Rahmawati, Ima; Ihsan, Muzhir (SAHID MENGABDI: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2025)
The training on developing Doratoon-based learning media incorporating local wisdom for elementary school teachers in Pamijahan District,Bogor Regency,aims to enhance teachers’ competence in integrating cultural values into classroom instruction.The program was implemented through a participatory workshop that combined experiential learning and learning by doing, and followed the stages of service learning:needs investigation (surveys,interviews,observations), material planning, hands-on practice in creating Doratoon media, and reflective discussion.Evaluation was conducted using observation sheets, product assessments, and participant questionnaires to measure improvements in technical skills, pedagogical competence, and the ability to embed local wisdom in learning media. The results indicate increased teacher capability in designing digital media that are contextual, creative, and culturally relevant, as well as readiness to apply them in classroom practice. This program contributes to improving the quality of elementary education and preserving local cultural values through their integration into instructional materials, and recommends continued mentoring for classroom implementation.